Analisis profil pelajar pancasila dimensi beriman, bertakwa kepada tuhan yang maha esa, dan berakhlak mulia pada mata pelajaran IPAS fase c sekolah dasar di kota Surakarta - Sofiana Ayu Rachmawati; Supianto Supianto (Didaktika Dwija Indria, 2025)
This study aims to give an overview of the measurement of the Pancasila Student Profile, especially the dimensions of faith, piety to God Almighty, and noble character in the Social and Science subject at phase C. This study uses a quantitative descriptive method. The subjects were 170 students phase C (grades V and VI) who spread across one elementary school in Surakarta City, namely SDN Tirtoyoso No. 111, SDN Tempel, and SDN Pasar Kliwon. Questionnaire was a way to collect data in this study, consisting of four elements and eight indicators used to measure the probability of faith, piety to God Almighty, and noble character. The general measurement results for all students were dominated by the very good and good categories. Students in the very good category were 45% and the good category were 36%. The rest were students in the sufficient category, at 8%, and the poor category, at 11%. The percentage of these results indicates that more students have an attitude of faith, piety to God Almighty, and noble character in the Social and Science subject.